Software-Defined Networking: Concepts and Applications - Sharma, Rishabh; Mahalwar, Abha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Software-Defined Networking (SDN) is a revolutionary paradigm that has transformed the way networks are designed, deployed, and managed. By decoupling the control plane from the data plane, SDN provides centralized control and programmability, offering numerous advantages over traditional networking approaches. This paper provides a comprehensive review of SDN concepts and applications, focusing on key aspects such as architecture, fundamentals, challenges, and future directions. We begin with an introduction to SDN, discussing its definition, evolution, and relevance in modern networking. We then delve into the fundamentals of SDN, exploring its key components, architecture, and control plane functionality. Next, we examine various SDN applications, including network management, traffic engineering, security, and cloud computing. We also discuss the challenges facing SDN, such as scalability, security, and interoperability, and highlight emerging trends and future research directions in the field. Through this review, we aim to provide a comprehensive understanding of SDN's impact on modern networking and its potential for future innovation.